Kecerdasan Emosi, Self-Esteem Dan Psychological Well-Being Pada Relawan Covid-19 - Aziza Fitriah; Dyta Setiawati Hariyono; Adinda Widya Ramadhana Putri (Jurnal Studia Insania, 2022)
This study aims to determine how the influence of Emotional Intelligence and self-esteem on psychological well being on Covid-19 Volunteers in the group MCCC (Muhammadiyah Covid-19 Command Center). The method used in this research uses quantitative methods, the aim of the researcher is to determine the effect of the Emotional Intelligence & self-esteem variable on the psychological well-being in volunteers. The instruments used in this study are 3 measurement scales, the Emotional Intelligence Inventory (EII) scale, the Self-Esteem Scale (RSES), the psychological Well-being scale. Based on the results of the data, it is known that of the two variables, namely emotional intelligence and self-esteem, one of the variables does not have a significant relationship to psychological well being in Covid-19 volunteers, the emotional intelligence variable. The self-esteem variable has a relationship and influence of 31.3%, which is quite strong on psychological well being in Covid-19 volunteers